Intraocular lens calculations in patients with keratoectatic disorders. Issue 4 (July 2020) - Smith, Ryan G.; Knezevic, Alexander; Garg, Sumit
Abstract : Purpose of review: Intraocular lens (IOL) calculations in patients with keratoconus and other keratoectatic disorders continues to be a challenge for today's cataract surgeon. In this article, we review data published over the past 18 months (June 2018 to January 2020). Recent findings: Cataract surgery in keratoconus patients has the potential to greatly improve patients' vision. However, keratoconic eyes are notorious for unpredictable outcomes because of difficulty in obtaining proper preoperative biometry and lack of data and consensus on IOL calculation formulas that can reliable in providing the desired outcome. Recent studies suggest the Barrett II Universal calculation is the most accurate in mild-to-moderate keratoconic eyes. All studies note the level of predictability decreases with the steepness of keratometric readings. Historically, the SRK/T has been shown to provide the most reliable calculations. Summary: There is still no consensus on which formula is best for IOL calculation in keratoconic eyes. On the basis of the most recent literature, we recommend using the Barrett II Universal in conjunction with the SRK/T formula for mild-to-moderate eyes. Preoperative counseling of expectations with the patient is the key to achieving a satisfied patient and avoiding an unpleasant situation in the result of refractive surprise.